Pendampingan dan Pelatihan Pengolahan Abon dan Kerupuk Ikan Bagi UMKM di Desa Pinang Habang Kabupaten Hulu Sungai Utara - Khairina, Rita; Normelani, Ellyn; Nasrudin, Nasrudin (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
Pinang Habang Village is one of the villages in Central Amuntai Sub-District, Hulu Sungai Utara Regency. The population of 607 consists of 307 men and 300 women. This village is an area of ??watery peatland throughout the year. The livelihood of the largest population is fishing and raising ducks. Fishing can be done throughout the year, the types of fish caught are cork (Channa striata), betok (Anabas testudineus), siam spikes (Trichogaster pectoralis), ponds (Helostoma sp.) And swamp fishing (Trichopterus sp.). All types of fish are sold fresh and only a few are processed into processed products. At the beginning of the dry season the production of catches is abundant so that fish tend to be untreated and rotten. Therefore, fisheries product processing technology is needed to overcome it. Through the program of the Peat Restoration Agency in 2018, efforts were made to revitalize the economy of the peat community in Pinang Habang by training and assisting in the processing of shredded cork fish and cork fish crackers. Participants consisted of 20 housewives divided into two groups. Each group is a community economic team focused on one processed product. The training activities began with the dissemination of activities, training on the processing of shredded cork fish, and cork fish crackers. After they are able to process the product, they are given assistance in packaging, labeling, promotion and marketing. The participants' responses during the activities were very positive and the spirit of entrepreneurship emerged when training and capital were provided in the form of equipment and raw materials. Assistance to them continues until all groups succeed independently.